Daredevil he man without fear. Ultimate collection. Book 2 - Brian Michael Bendis; Alexander Maleev (New York : Marvel Comics, ©, 2010)
Daredevil -- (Fictitious character from Marvel Comics Group) Daredevil (Fictitious character) -- Comic books, strips, etc. Heroes -- Comic books, strips, etc.